I am not a witch [videorecording (DVD)] - Mulilo, Nancy; Mulubwa, Margaret; Nyoni, Rungano; Nyoni, Rungano; Phiri, Henry B.J (Film Movement series., 2018)
When eight-year-old Shula turns up alone and unannounced in a rural Zambian village, the locals are suspicious. A minor incident escalates to a full-blown witch trial, where she is found guilty and sentenced to life on a state-run witch camp. There, she is tethered to a long white ribbon and told that if she ever tries to run away, she will be transformed into a goat. As the days pass, Shula begins to settle into her new community, but a threat looms on the horizon. Soon she is forced to make a difficult decision-whether to resign herself to life on the camp, or take a risk for freedom.